Energy expenditure of red-footed tortoises (Chelonoidis carbonaria) fed kibble diets with high levels of fibre, starch, or fat - Di Santo, Ludmilla G. [UNESP]; Pacheco, Letícia G. [UNESP]; Fernandes, Márcia H. M. R. [UNESP]; Braos, Lucas B. [UNESP]; Sanfilippo, Luiz F.; Scarpim, Lucas B. [UNESP]; Carciofi, Aulus C. [UNESP] (Taylor & Francis, 2022)
Knowledge of energy requirements is necessary to optimise the nutritional management of animals. For tortoises, very little is known about their nutrient and energy requirements. Data on substrate oxidation and the implications of starch or fat intake on the energy metabolism are lacking. The present study compared the daily energy expenditures (DEE) of red-footed tortoises (Chelonoidis carbonaria) that were fed three extruded diets: a control diet high in fibre and two test diets, one with high starch content and another with high fat content. A total of 18 tortoises (5.5 ± 1.18 kg) were used in a completely randomised design, with 6 animals per diet. After 14 months of experimental diet intake and 48 h of preliminary fasting, the animals were kept for 12 h in 70-l respiratory chambers. An open “push mode” system was used to determine the carbon dioxide production and oxygen consumption levels for the subsequent calculations of DEE. The data were analysed with ANOVA, and the means were compared by using Tukey’s test (p < 0.05). The body weights, chamber temperatures and food intakes of the tortoises were similar among the treatments (p > 0.05). There were no significant differences in oxygen consumption (21.7 ± 3.16 ml · kg−1 · h−1), carbon dioxide production (18.1 ± 1.96 ml · kg−1 · h−1), or DEE (9.7 ± 1.04 kJ · kg−1 d−1) between diets or sex (p > 0.05). The respiratory quotients (0.84 ± 0.11) were also similar among the diets (p > 0.05). The DEE of red footed tortoises did not differ after a long-term starch or fat intake.
Keywords: Metabolic rate; nutrition; oxygen consumption; reptiles; respirometry